Pengembangan Alat Penggorengan Modern Berbasis QFD dan Analisis SWOT untuk Meningkatkan Efisiensi dan Keamanan Pengguna - Kalista, Anggia; Muhyidin Agus Wibowo, Moh.; Dhini Anggraini, Susanti; Az-zahro', Sholihah (Industrial Engineering, Engineering of Faculty, Universitas Kadiri, 2024)
The rapid development of the food industry along with the increasing mobility of the community drives the demand for more sophisticated, hygienic, and efficient kitchen utensils. However, frying utensils that are still often used have weaknesses, such as uneven heat distribution and less than optimal residue filtration. This can reduce product quality and production efficiency, so improvements are needed to maintain product consistency and quality. This research aims to redesign the frying device. The SWOT method in this study helps to identify weaknesses and opportunities for improvement in traditional frying utensils and the Quality Function Deployment (QFD) method is used to identify user needs. The results of the study show that the development of this new frying device has proven to be more efficient compared to traditional convex pans, especially in a more even distribution of heat. With the addition of thermostat features, kitchen timer, gas detector, and waste filtration system. These innovations not only improve efficiency and convenience, but also provide additional protection for user safety.